Let's do some calculus! (62)

Calculus Level 4

π / 2 π / 2 e x cos ( tan 2 ( x ) ) ( 1 + cos ( 2 x ) ) ( 1 + e x ) d x = a π b c \large \displaystyle \int_{-{\pi}/{2}}^{{\pi}/{2}} \frac{e^x \cos (\tan ^2 (x))}{(1+\cos (2x))(1+e^x)} \,dx = \frac{a\sqrt{\pi}}{b\sqrt{c}}

where a , b , c a, b, c are integers with c c square-free and gcd ( a , b ) = 1 \text{gcd} (a, b) = 1 . Find the value of a + b + c a+b+c .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Jun 28, 2019

The integral is 1 2 π 1 2 π e x cos ( tan 2 x ) ( 1 + cos 2 x ) ( e x + 1 ) d x = 1 2 1 2 π 1 2 π cos ( tan 2 x ) 1 + cos 2 x d x = 1 4 1 2 π 1 2 π cos ( tan 2 x ) sec 2 x d x = 1 4 cos ( x 2 ) d x = π 4 2 \begin{aligned}\int_{-\frac12\pi}^{\frac12\pi} \frac{e^x \cos(\tan^2x)}{(1 + \cos2x)(e^x+1)}\,dx &= \; \tfrac12\int_{-\frac12\pi}^{\frac12\pi} \frac{\cos(\tan^2x)}{1+ \cos2x}\,dx \\ & = \; \tfrac14\int_{-\frac12\pi}^{\frac12\pi}\cos(\tan^2x)\,\sec^2x\,dx \\ & = \; \tfrac14\int_{-\infty}^\infty \cos(x^2)\,dx \; = \; \tfrac{\sqrt{\pi}}{4\sqrt{2}} \end{aligned} for a solution of 1 + 4 + 2 = 7 1 + 4 + 2 = \boxed{7} .

A minor typo in the second line Sir.......there is a \b \displaystyle \b appearing before the d x \displaystyle dx

Aaghaz Mahajan - 1 year, 11 months ago
N. Aadhaar Murty
Oct 6, 2020

We have

I = π 2 π 2 e x cos ( tan 2 x ) ( 1 + cos 2 x ) ( 1 + e x ) d x = 1 2 π 2 π 2 cos ( tan 2 x ) cos 2 x ( 1 + e x ) d x I = \int_{\frac {-\pi}{2}}^{\frac {\pi}{2}} \frac {e^{x}\cos(\tan^{2}x)}{(1+\cos2x)(1+e^{x})} dx = \frac {1}{2}\int_{\frac {-\pi}{2}}^{\frac {\pi}{2}} \frac{\cos(\tan^{2}x)}{\cos^{2}x(1+e^{-x})} dx

Now, using the property a b f ( x ) d x = a b f ( a + b x ) d x \int_{a}^{b} f(x) dx = \int_{a}^{b} f(a+ b-x) dx ,

I = 1 2 π 2 π 2 cos ( tan 2 x ) cos 2 x ( 1 + e x ) d x I = \frac {1}{2} \int_{\frac {-\pi}{2}}^{\frac {\pi}{2}} \frac {\cos(\tan^{2}x)}{\cos^{2}x(1 + e^{x})} dx

as tan 2 x \tan^{2}x and cos 2 x \cos^{2}x are both even functions.

2 I = 1 2 π 2 π 2 ( e x + 1 ) cos ( tan 2 x ) cos 2 x ( 1 + e x ) = 0 π 2 cos ( tan 2 x ) ( cos 2 x ) \therefore 2I = \frac {1}{2} \int_{\frac {-\pi}{2}}^{\frac {\pi}{2}} \frac {(e^{x}+1)\cos(\tan^{2}x)}{\cos^{2}x(1+e^{x})} = \int_{0}^{\frac {\pi}{2}} \frac {\cos(\tan^{2}x)}{(\cos^{2}x)}

Substituting tan x = u \tan x = u , we get the Fresnel integral as x x \to \infty

2 I = 0 cos ( u 2 ) d u = π 8 = π 2 2 I = π 4 2 2I = \int_{0}^{\infty} \cos(u^{2}) du = \sqrt {\frac {\pi}{8}} = \frac {\sqrt {\pi}}{2\sqrt{2}} \Rightarrow I = \frac {\sqrt {\pi}}{4\sqrt {2}}

a + b + c = 7 \boxed{\therefore \Large {a + b + c = 7}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...